2011
DOI: 10.1203/pdr.0b013e3182111827
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Enterocolitis Is Associated With Ureaplasma Colonization in Preterm Infants

Abstract: The study objective was to determine whether Ureaplasma respiratory tract colonization of preterm infants <33 weeks gestation is associated with an increased risk for necrotizing enterocolitis (NEC). One or more tracheal or nasopharyngeal aspirates for Ureaplasma culture and PCR were obtained during the first week of life from 368 infants <33 weeks gestation enrolled from 1999-2003 or from 2007-2009. NEC Bell stage ≥2 was confirmed by radiological criteria, and pathology, if available. Cord serum samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 46 publications
2
48
0
Order By: Relevance
“…This notion is conceptually correct because Ureaplasma parvum and Ureaplasma urealyticum are the most common organisms isolated from infected amniotic fluid, and are associated with preterm labor (59). Respiratory colonization with Ureaplasma doubles the risk of developing NEC in very preterm infants (60). The association of Ureaplasma with NEC still requires the molecular presence Review of this microbe in either surgical specimens or feces of infants who develop NEC.…”
Section: Gba Interactions With Gut Microbiota Epithelia and Immune mentioning
confidence: 99%
“…This notion is conceptually correct because Ureaplasma parvum and Ureaplasma urealyticum are the most common organisms isolated from infected amniotic fluid, and are associated with preterm labor (59). Respiratory colonization with Ureaplasma doubles the risk of developing NEC in very preterm infants (60). The association of Ureaplasma with NEC still requires the molecular presence Review of this microbe in either surgical specimens or feces of infants who develop NEC.…”
Section: Gba Interactions With Gut Microbiota Epithelia and Immune mentioning
confidence: 99%
“…Ureaplasma infection induces production of tumor necrosis factor-α and interleukin-6 [11] and also causes apoptosis of human type 2 lung epithelial cells and lung macrophages [12]. Apart from BPD, Ureaplasma has also been associated with retinopathy of prematurity [13], intraventricular hemorrhage [14,15], necrotizing enterocolitis (NEC) [16] and adverse neurodevelopmental outcome [17]; all these associations could be attributed to the ability of Ureaplasma to elicit an inflammatory reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Ureaplasma has been detected in gastric aspirate samples from preterm human neonates, and experimental intrauterine Ureaplasma infection in pregnant sheep was found to impair development of the fetal ovine gut in an IL-1-dependent manner. 12,13 In addition, Okogbule-Wonodi et al, 14 have reported a 2-fold increased NEC prevalence in Ureaplasma-infected neonates born <33 weeks and a 3.3-fold increase in those born <28 weeks with Ureaplasma infection.…”
Section: Discussionmentioning
confidence: 97%